Informacijos apie įmonę iškraipymo būdai ir padariniai - Lakis, Vaclovas (Information & Media, 2009)
Straipsnyje nagrinėjami išorės ir vidaus veiksniai, kurie gal turėti įtakos informacijai apie įmonės finansinę būklę ir veiklos rezultatus iškraipyti. Apžvelgiami duomenų apie turtą, įsipareigojimus, pajamas, sąnaudas, pelną iškraipymo būdai. Išryškinama infliacijos įtaka pateiktų duomenų objektyvumui ir tyčinio duomenų iškraipymo pavojai. Remiantis duomenimis apie Lietuvoje tiriamų baudžiamųjų bylų pobūdį, Finansinių nusikaltimų tyrimo tarnybos darbo ataskaitomis ir bankrotų statistika mėginama įvertinti nagrinėjamos problemos mastą ir padarinius. Pagrindiniai žodžiai: finansinės ataskaitos, ekonominė informacija, informacija apie įmonę, informacijos iškraipymas, įsipareigojimai, pajamos, sąnaudos, pelnas, iškraipymo būdai. Ways and consequences of information fraud about an enterprise Vaclovas Lakis Summary In today’s global world, every legal entity is entitled to get a reliable information about other companies if their relationship is based on finance, production, cooperation, trade, etc. Usually, everybody believes that the situation in the company they are interested in will be under constant improvement and will never get worse. However, in the real world, a company’s financial status and its performance results for different reasons can fluctuate. In turn, such negative consequences can influence a company’s performance and make a negative impact on managers, because investors, creditors and partners hardly tolerate them. Companies experiencing a constant pressure try in permissible ways to depict the company’s activity as being stable and reliable. This is done using permissible standards but an inappropriate combination of means which distort the company’s performance and financial state. Moreover, sometimes information is mispresented and distorted to such extent that a correct information about the company’s assets and activity is impossible. Conscious distortions are most dangerous for legal entities when documents are a fraud, the enterprise’s performance and activities undergo distortion too, and registered data presented in financial statements and accountancy do not depict the real situation. The value of a company’s assets and liabilities provides good possibilities to cover all the debts owed to creditors and to continue the company’s performance. The value of fixed assets can be distorted, if the depreciation was not estimated at all or the calculation was done wrongly. In accountancy, if the depreciation value is presented as being smaller, it means that the cost price decreases and the profit increases. Sometimes, because of the maintenance and reconstruction of the fixed assets, their quality did not improve, or the usage did not prolong; it means that the expenses increase the cost price of the current period. In order to improve the company’s image, the value of fixed assets is increased by the amount of incurred expenses. It means that in a certain period of time the profit increases and in other periods decreases without a real ground because of the increased depreciation of assets. There are cases when fixed assets must be adjusted. If this is not done, the information about the company’s performance is incorrect. Company’s liabilities can be concealed if the classification does not correspond to a true picture, if the invoices and guarantees are not provided, if the real debt value is not given and can increase because of interest or fine. The amount of revenue and expenditure makes an impact on the company’s profit, so the company tries to show an increase of revenues and a decrease of expenditure. Consequently, if the company wants to show a decrease of profit, the situation is inverse. The amount of revenues can be distorted by manipulating with the company’s transactions. The amount of expenditure is decreased intentionally either directly or indirectly changing the terms of time. Moreover, profit can be distorted too, if transactions with other companies do not depict the real picture; as a result, the price of fixed and current assets is much bigger than the market price. The assets acquired by the third party are sold at the market price, i.e. experiencing great losses. If the financial statements depicting the value of assets which are bought and sold are consolidated, the following step is elimination of transactions from the consolidated financial statements of different enterprises. Using the distorted information about a company, other legal and physical entities make erroneous decisions. Losses due to such decisions made on the basis of distorted financial statements are very big. Very often such distortions lead to bankruptcies. In the period from 1993 to 2007, the value of the companies that underwent or were on the verge of bankruptcy was 6421,42 million Lt and the debt to creditors 9216,80 million Lt.